Turystyka eventów sportowych w Poznaniu - aspekty społeczne, kulturowe i polityczne (ze szczególnym uwzględnieniem turnieju UEFA EURO 2012) = Sport event tourism in poznan – social, cultural and political aspects (with the special focus on UEFA EURO 2012) - Malchrowicz-Mośko, Ewa; Rozmiarek, Mateusz (Journal of Education, Health and Sport, 2016)
Malchrowicz-Mośko Ewa, Rozmiarek Mateusz. Turystyka eventów sportowych w Poznaniu - aspekty społeczne, kulturowe i polityczne (ze szczególnym uwzględnieniem turnieju UEFA EURO 2012) = Sport event tourism in poznan – social, cultural and political aspects (with the special focus on UEFA EURO 2012). Journal of Education, Health and Sport. 2016;6(10):158-174. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.160524 http://ojs.ukw.edu.pl/index.php/johs/article/view/3931 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 12.10.2016. TURYSTYKA EVENTÓW SPORTOWYCH W POZNANIU – ASPEKTY SPOŁECZNE, KULTUROWE I POLITYCZNE (ZE SZCZEGÓLNYM UWZGLĘDNIENIEM TURNIEJU UEFA EURO 2012) SPORT EVENT TOURISM IN POZNAN – SOCIAL, CULTURAL AND POLITICAL ASPECTS (WITH THE SPECIAL FOCUS ON UEFA EURO 2012) Ewa Malchrowicz-Mośko1, Mateusz Rozmiarek2 1 Katedra Humanistycznych Podstaw Turystyki i Rekreacji, Akademia Wychowania Fizycznego w Poznaniu Department of Cultural Basic of Tourism, University School of Physical Education In Poznań 2 Instytut Nauk Społecznych, Pracownia Olimpizmu, Akademia Wychowania Fizycznego w Krakowie Institute of Social Sciences, Olympism Department, University of Physical Education in Kraków Słowa kluczowe: event sportowy, turystyka eventów sportowych, Poznań, UEFA EURO 2012 Key words: sport event, sport event tourism, Poznan, UEFA EURO 2012 Streszczenie Celem artykułu jest określenie potencjału turystyki eventów sportowych w Poznaniu. W pracy dokonano analizy imprez sportowych, które od kilku lat odbywają się w Poznaniu (cyklicznie lub niecyklicznie). Scharakteryzowano również ich wymiar społeczno-kulturowy oraz wybrane wątki polityczne. Szczególny nacisk położony został na opis mega-wydarzenia sportowego, które miało miejsce w stolicy Wielkopolski w 2012 roku – turnieju UEFA EURO 2012. Abstract The aim of this article is to determine the potential of sport event tourism in Poznan. The study analyzes sporting events, which for several years held in Poznan (cyclic or acyclic). Also they characterized their socio- cultural and political themes selected. Particular emphasis has been placed on the description of the mega-sporting event, which took place in the capital of Wielkopolska in 2012 - UEFA EURO 2012.